2004
DOI: 10.1002/cd.113
|View full text |Cite
|
Sign up to set email alerts
|

Girls' and boys' developing interests in math and science: Do parents matter?

Abstract: Previous studies (for example, Bregman & Killen, 1999; Eccles, Wigfield, & Schiefele, 1998; Jacobs, 1991;Jacobs & Eccles, 2000) have demonstrated the important role that parents' attitudes play in shaping their children's later self-perceptions and achievement behaviors. Studies indicate that in the math and science arena, parents' perceptions of their children's abilities as well as their own values about math and science are related to their children's later self-perceptions and values for achieving in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
3
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 34 publications
6
90
3
10
Order By: Relevance
“…8 Working within this framewo rk, Bleeker and Jacobs (2004) and Jacobs and Bleeker (2004) present results in support of a claim that a mother's belief about her children's science competence affects whether her daughters and sons develop a greater interest in science compared to other pursuits. 9 Among high school seniors in the 1992 NELS, the unadjusted female-to-male odds ratio for intending to complete a science or engineering major is 0.3 1;…”
Section: Occupational Plans and College Major Selectionsupporting
confidence: 54%
“…8 Working within this framewo rk, Bleeker and Jacobs (2004) and Jacobs and Bleeker (2004) present results in support of a claim that a mother's belief about her children's science competence affects whether her daughters and sons develop a greater interest in science compared to other pursuits. 9 Among high school seniors in the 1992 NELS, the unadjusted female-to-male odds ratio for intending to complete a science or engineering major is 0.3 1;…”
Section: Occupational Plans and College Major Selectionsupporting
confidence: 54%
“…half of 1045+922) were to have continued this would have increased mathematics participation by nearly 10% overall. The increasing body of research into girls' attitudes to the study of mathematics (Fennema & Leder, 1990;Jacobs & Bleeker, 2004;Mendick, 2005;Solomon, 2007) suggests that the female participation issue emerges at a much younger age and therefore it would need to be tackled well before these students approached the age at which they are expected to decide on advanced studies.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature has consistently reported that parents' and peers' attitudes and behaviour towards mathematics represent two major environmental influences on children's formation of academic attitudes (Jacobs & Bleeker, 2004;Jacobs & Eccles, 2000;Ryan & Patrick, 2001;Tiedemann, 2000;Yee & Eccles, 1988). Studies by researchers such as Armstrong (1980), Eccles (1983), Jacobs andBleeker (2004), and Jacobs and Eccles (2000) have suggested that parents' beliefs about mathematics might contribute to their children's mathematics course enrolment decisions.…”
Section: Subjective Normsmentioning
confidence: 99%
“…Studies by researchers such as Armstrong (1980), Eccles (1983), Jacobs andBleeker (2004), and Jacobs and Eccles (2000) have suggested that parents' beliefs about mathematics might contribute to their children's mathematics course enrolment decisions. Jacobs and Bleeker (2004) also reported that parents' mathematics-promoting behaviour was related to their children's later interests and activities.…”
Section: Subjective Normsmentioning
confidence: 99%